Properties of palm oil fuel ash cement based aerated concrete - Khairunisa, Muthusamy (2009)
Utilization of palm oil fuel ash (POFA) which is an abundantly generated waste by Malaysian palm oil industry in producing a new construction material is seen as one of the ways to reduce the quantity of this by-product disposed at landfill. This thesis presents an experimental study on the engineering properties and durability of aerated concrete consisting of POFA as partial cement replacement, known as POFA cement based aerated concrete. Two types of mixes are prepared. One consists of a control mix whereas another one consists of 20 percent of POFA. The latter has been found to give the highest strength as compared to any other replacements. More than one thousand specimens comprising cubes (70.6 x 70.6 x 70.6 mm), panels (540 x 250 x 25 mm), mortar bars (25 x 25 x 250 mm) and prisms (40 x 40 x 160 mm), (40 x 40 x 50 mm) and (225 x 225 x 25 mm), plates (650 x 100 mm) and (885 x 270 x 25 mm) have been tested in this study. The influences of POFA with numerous replacement level and mixing constituents on compressive strength of aerated concrete have been investigated. The effects of curing methods on the compressive and flexural strengths of the specimens up to one year are also studied. Studies on the durability aspect of the mix are conducted to investigate its acid resistance, sulphate resistance, performance in sea water, carbonation, dimensional stability, as well as fire resistance. POFA aerated concrete is then used to produce panels for the investigation of their compressive strength. The experiments reveal that continuous water curing is the best method in assisting POFA aerated concrete for a higher strength than the ordinary Portland cement (OPC). A constant presence of moisture is significant for the strength development of POFA aerated concrete since pozzolanic reaction can only take place at the later age, after calcium hydroxide is available from the hydration. Utilization of POFA in aerated concrete improves the durability of the lightweight concrete when exposed to aggressive environment, such as acid, sulphate and sea water. The weight loss for OPC specimen is 3.94% from its original weight as compared to POFA aerated concrete which lost only 0.9% when immersed in hydrochloric acid solution for 1800 hours. Upon exposure to 10% sodium sulphate solution, OPC mortar bar exhibit map cracks and expand as much as 14 times higher than POFA specimen. Besides that, POFA specimens also demonstrate higher durability to sea water when it exhibits lower strength reduction compared to plain aerated concrete after an exposure to marine environment for one year. The non combustible characteristic of this product and a very low influence on fire growth fulfills the requirement of the highest Class 0 under Clause 204A in Building By-Law (1984). Finally, the study shows that POFA aerated concrete mix can be used to produce panels with adequate x 25 strength as non load-bearing element in construction.